Eletrofiação e caracterização de membranas biopoliméricas a base de quitosana extraídas dos exoesqueletos de crustáceos - Andrade, Sânia Maria Belísio de (2012)
Chitin and chitosan are nontoxic, biodegradable and biocompatible polymers produced by renewable natural sources with applications in diverse areas such as: agriculture, textile, pharmaceutical, cosmetics and biomaterials, such as gels, films and other polymeric membranes. Both have attracted greater interest of scientists and researchers as functional polymeric materials. In this context, the objective of this study was to take advantage of the waste of shrimp (Litopenaeus vannamei and Aristeus antennatus) and crabs (Ucides cordatus) from fairs, beach huts and restaurant in Natal/RN for the extraction of chitin and chitosan for the production of membranes by electrospinning process. The extraction was made through demineralization, deproteinization, deodorization and deacetylation. Morphological analyzes (SEM and XRD), Thermal analysis (TG and DTG), Spectroscopy in the Region of the Infrared with Transformed of Fourier (FTIR) analysis Calorimetry Differential Scanning (DSC) and mechanical tests for traction were performed. In (XRD) the semicrystalline structure of chitosan can be verified while the chitin had higher crystallinity. In the thermal analysis showed a dehydration process followed by decomposition, with similar behavior of carbonized material. Chitosan showed temperature of maximum degradation lower than chitin. In the analysis by Differential Scanning Calorimetry (DSC) the curves were coherent to the thermal events of the chitosan membranes. The results obtained with (DD) for chitosan extracted from Litopenaeus vannamei and Aristeus antennatus shrimp were (80.36 and 71.00%) and Ucides cordatus crabs was 74.65%. It can be observed that, with 70:30 solutions (v/v) (TFA/DCM), 60 and 90% CH3COOH, occurred better facilitate the formation of membranes, while 100:00 (v/v) (TFA/DCM) had formation of agglomerates. In relation to the monofilaments diameters of the chitosan membranes, it was noted that the capillary-collector distance of 10 cm and tensions of 25 and 30 kV contributed to the reduction of the diameters of membranes. It was found that the Young s modulus decreases with increasing concentration of chitosan in the membranes. 90% CH3COOH contributed to the increase in the deformation resulting in more flexible material. The membranes with 5% chitosan 70:30 (v/v) (TFA/DCM) had higher tensile strength